A RANDOMIZED TRIAL COMPARATIVE STUDY OF THE IMPACT OF ADDING CLONIDINE TO BUPIVACAINE AND USING BUPIVACAINE ALONE FOR AXILLARY BRACHIAL PLEXUS BLOCK - Kumar, Rajeev; Piyush, Akhil; Sharma, Shalini; Prasad, Sudama (Student’s Journal of Health Research Africa, 2024)
Background Numbing a specific nerve or a group of nerves with a shot of medicine is an essential part of anesthesia. Especially people who cannot bear general anesthesia during a procedure or suffer from hemodynamic instability consider peripheral nerve blockade as a primary substitute. Clonidine is an antihypertensive drug (α2 agonist) when used as an adjuvant to bupivacaine (a powerful local anesthetic), it may increase the period of blocks. This study aims to compare and evaluate the adjuvant effect of clonidine with bupivacaine and solo bupivacaine for “axillary brachial plexus block". Methods A randomized, controlled, prospective study was conducted involving 60 participants undergoing hand or forearm surgeries. Participants were divided into two groups: Group 1 received clonidine (0.8 ml, 120 µg) + normal saline (0.2 ml) + bupivacaine (25 ml, 0.5%), and Group 2 received normal saline (1 ml) + bupivacaine (25 ml, 0.5%). The onset time and duration of motor and sensory blocks were recorded. Results Group 1 had a significantly faster onset of nerve block and a longer duration of motor (440.5 ± 42.28 min vs. 198.43 ± 27.96 min) and sensory blocks (339.57 ± 40.82 min vs. 212.83 ± 35.25 min) compared to Group 2. These differences were statistically significant (p < 0.001). No major side effects were observed in either group. Conclusion This study clearly shows that the effect of adjuvant clonidine fastens the onset of nerve blockade and also gives a longer duration of analgesic effect to the patients without producing any major side effects. Recommendation Based on the findings, the study recommends using clonidine as an adjuvant to bupivacaine for axillary brachial plexus blocks in clinical practice, especially in cases where prolonged anesthesia and analgesia are desired, and minimal side effects are essential.